2008
DOI: 10.1093/beheco/arn014
|View full text |Cite
|
Sign up to set email alerts
|

A growth cost of experimentally induced conspicuous coloration in first-year collared lizard males

Abstract: I used painted first-year collared lizard males in the field to test the hypothesis that conspicuous coloration imposes a growth cost, either because it makes lizards less cryptic to their prey or because conspicuous color attracts predators forcing increased refuging by lizards. To make males more conspicuous, I painted them green and yellow to match hues of older territorial males, made another group inconspicuous by painting males brown like females, and painted a control group with water. I then compared r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Recently, Baird (2008) demonstrated that femalecoloured yearling male C. collaris, painted to resemble more conspicuous adult males, grew significantly more slowly than did control yearling males (painted brown or painted with water). The results showed that the more conspicuously painted young males made fewer attempts to attack prey and that, when they did attack, they were less successful than control males.…”
Section: Interaction Of Natural and Sexual Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Baird (2008) demonstrated that femalecoloured yearling male C. collaris, painted to resemble more conspicuous adult males, grew significantly more slowly than did control yearling males (painted brown or painted with water). The results showed that the more conspicuously painted young males made fewer attempts to attack prey and that, when they did attack, they were less successful than control males.…”
Section: Interaction Of Natural and Sexual Selectionmentioning
confidence: 99%
“…The results showed that the more conspicuously painted young males made fewer attempts to attack prey and that, when they did attack, they were less successful than control males. Baird (2008) attributed the slower growth rates in the experimental males to a reduction in 'aggressive crypsis ' (Endler, 1981); that is, being more conspicuous resulted in early detection by prey (Grether & Grey, 1996). Thus, conspicuous ornamental coloration should be particularly costly for collared lizards, which are predators as well as prey.…”
Section: Interaction Of Natural and Sexual Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as Bonnet et al (2000) suggest for Vipera aspis, an intermediate body size would balance ecological and reproductive advantages, maximizing the reproductive output. Body size has a strong influence on reproductive output but also on the ecological consequences for an organism, since overall energy balance is strongly affected by body size (Baird 2008). High maintenance requirements of larger individuals may increase their vulnerability in low-resource habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Energy allocation to growth and reproduction determines life history structure (Stearns 1992;Baird 2008). Body size is a key life-history trait because it determines many aspects of the biology of organisms and their interaction with the environment (Naganuma and Roughgarden 1990).…”
mentioning
confidence: 99%